Integration of Atmospheric Sensors into Unmanned Aerial Vehicle Platforms - Kennedy, Matthew; Bui, Peter (My University, 2015)
Applications of Unmanned Aerial Vehichles (UAVs) are being investigated at University of Wisconsin--Eau Claire as part of a Geospatial Education Initiative. The purpose of this study was to find the goal for full integration of sensor control and data acquisition for real-time data output through the on-board auto-pilot feature so that the UAV flight can be adjusted for observed atmospheric conditions.
Color poster with text, photographs, and images.
Keywords: Flight data; Atmospheric sensors; Posters; Applications of Unmanned Aerial Vehicles (UAVs)